Open space management: Issues and problems - Ibrahim, Putri Haryati; Md Dali, Melasutra; Che Haron, Roziha (2016)
This study aimed to identify and understand the problems faced by local authorities in the management of open spaces in their area of administration. The study focused on the management of open spaces by 9g local authorities ,rn Peninsular Malaysia that are governed under the Town and country Pfanning Act 1976 (Act 172). Although numerous studies have examined the benefits of open space to human life, extra attention needs to be given to the aspect of management to ensure its sustainability. To obtain information on the management of open spaces that involves development, preparation and policy enforcement, questionnaire survey was distributed to 456 responoents nhich obtained a response rate of s2.6o/o (n=240). The study found that the arailability of land, lack of funding and policy compliance are the main obstacles hindering local authorities to provide better service to the public. This qtrudy recommends several measures to address the issues in the hope that it mll help the local authorities to better manage and provide long term sustainable open spaces.